Indirect employee expenditure analysis with zakat distribution as a moderation variable towards poverty in Indonesia - Nasrullah Arsyad Safin; Dhimasfaris Dananjaya (Indonesian Journal of Islamic Economics Research, 2021)
This study aims to determine the effect of indirect personnel spending on poverty through the moderating variable of the distribution of zakat by using panel data analysis of 34 provinces in Indonesia. The results reveal that it is found that the best model is the fixed effect model. In the fixed-effect model estimation, results obtained from the variable Indirect Employee Expenditures as well as indirect employee expenditures through the moderating variable zakat distribution to poverty 34 Provinces in Indonesia shows a positive effect